SOCIAL MEDIA MARKETING STRATEGY THROUGH INSTAGRAM AND FACEBOOK FOR MSMES IN SURABAYA CITY - Ayu Nadia Charissa (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
This study aims to determine the implementation of social media marketing through social media Facebook and Instagram carried out by SMEs in the city of Surabaya. The sample in this study is SMEs actors who use social media to market their products on Facebook and Instagram, domiciled in Surabaya. In this study, there were five SMEs actors in the city of Surabaya. This study uses a qualitative descriptive analysis approach. The results of this study indicate that SMEs in the city of Surabaya have implemented social media marketing through Instagram and Facebook in accordance with Silverstein's theory (2015).